DETERMINAN EKSPOR DI NEGARA-NEGARA ASEAN - Reca Rossa Arianty; Taufiq Carnegie Dawood (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2023)
The purpose of this study is to analyze the factors influencing exports of ASEAN countries from 2007-2021. This study used panel vector autoregressive (PVAR), and panel vector error correction (PVECM) analysis methods for data which is not stationary at the level and are cointegrated. The results showed that the exchange rate has a significant influence both in the long and short term on the volume of exports. There is also a negative relationship between the exchange rate and exports, in terms of output. In the long and short run, the US GDP variable has a significant influence on export volumes. The relationship between US GDP and exports is positive. Policy implication is that ASEAN countries should enact policies which support export competitiveness vis-à-vis trade partner countries. In addition, exchange rate policies can be considered to be used occasionally to help enhance exports.